An improved model for metal-hydrogen storage tanks – Part 2: Model results. (19th February 2016) - Mohammadshahi, Shahrzad S.; Gould, Tim; Gray, Evan MacA.; Webb, Colin J.
Abstract: An enhanced 3-D numerical model, described in Part 1 [1] of this two part work, has been employed to study a metal-hydrogen storage system. In this manuscript we investigate the effect of varying the hydrogen in-flow rate and total amount of hydrogen inserted on the time taken to absorb/store the hydrogen and the temperature excursions. In addition, the ability to vary the temperature of the thermal management fluid has been used to examine the relative effect of a fixed fluid temperature and one which is hotter for desorption and colder for absorption. It was found that a shorter time and a greater amount of hydrogen injection to the tank leads to a higher driving pressure and, as a result, higher rate of absorption. This must be moderated by constraints such as the pressure rating of the tank. Furthermore, compared to using the same constant temperature thermal fluid for absorption and desorption, switching the fluid temperature between 283 K for absorption and 343 K for desorption leads to faster hydrogen cycling and more complete hydrogen desorption in the tank. However, a constant fluid temperature of 313 K gives a reasonable performance over the same time duration, without the additional energy expenditure associated with switching the fluid temperature. Highlights: Improved multiphysics model for hydrogen storage MH tank applications. Study of effect of hydrogen injection amount and flow rate. Study of effect of hydrogen release flow rate. Absorption and desorption cycles start at conclusion of previous cycle. Study of effect of different thermal management temperatures.